Implementation of Production Cost Using the Full Costing Method at CV Tani Nias Makmur - Gloria Zefita Kristiani Zebua; Serniati Zebua; Eliagus Telaumbanua; Sophia Molinda Kakisina (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the implementation of the cost of production (HPP) calculation at a local manufacturing enterprise to determine whether the company has applied accurate and appropriate costing methods. The research focuses on identifying the components of raw material costs, labor costs, and factory overhead costs, as well as evaluating the suitability of the company’s costing approach with generally accepted accounting principles. Using a descriptive qualitative method, data were collected from interviews, documentation, and direct observation. The results show that the company has not fully implemented a comprehensive cost of production calculation, particularly in allocating factory overhead costs, which leads to inaccurate product pricing and profit assessment. The study concludes that proper cost of production implementation is essential for determining competitive pricing, evaluating business performance, and supporting managerial decision-making. It is recommended that the company adopt a more structured costing system to enhance accuracy and financial effectiveness.